Pengaruh Sifat Inovasi dan Faktor Sosial Ekonomi Terhadap Tingkat Adopsi Booster Murni pada Petani Kelengkeng - Utari Praba Ningrum; Epsi Euriga; Mastur Mastur (Journal of Food Security and Agroindustry, 2026)
Longan (Dimocarpus longan) is a high-value horticultural commodity with increasing market demand in Indonesia. However, its productivity still faces several constraints, particularly the limited application of optimal cultivation technologies. Booster Murni technology was developed as an innovation to stimulate flowering and fruiting in longan, thereby increasing crop productivity; however, its adoption level among farmers remains varied. This study aimed to analyze the effects of innovation attributes and socio-economic factors on the adoption level of Booster Murni among longan farmers in Moyudan and Minggir Kapanewon, Sleman Regency, Special Region of Yogyakarta. The study was conducted from December 2025 to May 2026 using a quantitative approach with multiple linear regression analysis. The entire population of 30 farmers using Booster Murni was selected as respondents through a census method. Data were collected using questionnaires. The results showed that the innovation attributes of Booster Murni were in the high category, with an achievement level of 80%, while the adoption level reached 83.7% and was also classified as high. Simultaneously, socio-economic factors and innovation attributes had a significant effect on the adoption level. Partially, only compatibility and observability had positive and significant effects on the adoption level, whereas age, education, land area, relative advantage, complexity, and trialability had no significant effect. The regression model explained 81.7% of the variation in adoption level. Therefore, improving the compatibility of the technology with farmers’ conditions and enhancing the ease of observing innovation outcomes should be prioritized to promote the sustainable adoption of Booster Murni.